2019
DOI: 10.1021/acs.jpcb.9b00680
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Primer-Treated Al2O3 Surfaces by Bisphenol A Diglycidyl Ether: Determination of the Mechanism from Molecular Dynamics Simulations and Experiments

Abstract: This study aims to develop a molecular dynamics (MD) simulation procedure to investigate the wettability of primer-treated Al2O3 surfaces by bisphenol A diglycidyl ether (BADGE) and to understand the interaction between the surface and the liquid. The MD simulation results were compared with those obtained by contact angle measurements, time-of-flight secondary ion mass spectrometry (TOF-SIMS), and atomic force microscopy (AFM) and were found to be in agreement with the experimental evaluations. The results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Then, the discrete data points of the oil/water interface were converted to the contact angle through the θ/2 method. 32,33…”
Section: Methodsmentioning
confidence: 99%
“…Then, the discrete data points of the oil/water interface were converted to the contact angle through the θ/2 method. 32,33…”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, many studies have investigated interfacial phenomena using computational techniques, such as density functional theory (DFT) and molecular dynamics (MD) calculations. Some have revealed that functional groups in polymers, such as amine, epoxy, and methacrylate groups, improve the interaction with metal/metal oxide surfaces, leading to a better bonding. Others examine the contributions of microstructures on metal/metal oxide surfaces. For example, Iwamoto studied an epoxy–copper oxide interface, revealing that roughness of the copper oxide surface increases the involvement of the polymer at the interface when a shear or tensile stress is applied, and that a higher contribution of the roughness is observed in a shear mode .…”
Section: Introductionmentioning
confidence: 99%